The influence of narrative medicine on medical students’ readiness for holistic care practice: a realist synthesis protocol - Lynn V Monrouxe; Yufrica Huang; Chien-Da Huang (BMJ Open)
Introduction Holistic healthcare considers the whole person—their body, mind, spirit and emotions—and has been associated with narrative medicine practice. Narrative medicine is medicine performed with narrative skill and has been offered as a model for humanism and effective medical practice. Narrative medicine interventions have been associated with physicians’ increased empathy and more meaningful interactions with patients about managing their illness and preventative medicine. However, while there is some evidence that certain groups are more open to narrative practices (eg, traditional vs Western medical students), the extent to which narrative medicine interventions during undergraduate medical education impacts on students’ readiness for holistic care, as well as the underlying reasons why, is unknown.Methods and analysis Realist review is a theory-driven approach to evaluate complex interventions. It focuses on understanding how interventions and programmes work (or not) in their contextual setting. This realist synthesis aimed to formulate a theory around the influence of narrative medicine medical students’ readiness for holistic care practice. We will follow Pawson’s five steps: locate existing theories, search strategy, study selection, data extraction, data analysis and synthesis. We will use the following electronic databases: Web of Science, Medline, Scopus and Embase. Articles between January 2008 and September 2018 will be included. Results will be written according to the RAMESES (Realist And Meta-narrative Evidence Syntheses: Evolving Standards) standard for reporting realist syntheses.Ethics and dissemination Ethics approval was obtained from the Chang Gung Memorial Hospital for the wider study. The findings of this review will provide useful information for academics and policymakers, who will be able to apply the findings in their context when deciding whether and how to introduce narrative medicine programmes into medical students’ curricula. We will publish our findings in peer-reviewed journals and international conferences.PROSPERO registration number CRD42018115447.